Basic Design Architecture of Congestion Notification System: A Real Time Road Traffic Information Enabler (Nigerian Journal of Technology, 2021)
Road traffic congestion is a prominent challenge of today’s urban center. As a push factor of urban centers, it impact negatively on socio-economic well-being of cities. However, contemporary innovative transport technology of Intelligent Transport System (ITS) is bridging the traveler information gaps, through installation and deployment of smart transport infrastructure such as Congestion Notification System at critical traffic intersections and points that aggravate road traffic congestion. This paper therefore provides a detailed explanation on the configuration and basic architecture of a primary Congestion Notification System (CNS) stating its working principles in providing real time road traffic congestion level information to motorist, prior entering the congestion zones or section of the road. Thus, engendering informed decision by motorists on alternative routes rather than the congested route.http://dx.doi.org/10.4314/njt.v40i1.1